Avtomatizacija postopka naprševanja na laboratorijskem visokovakuumskem sistemu - Berič, Boris (Kovine zlitine tehnologije, 1997)
The modern vacuum systems have valves and other elements PC or PLC controlled. For safety reasons all movements are checked in real time and adapted to real values of pressure temperature, current, thickness of sputtering layer, etching time etc. Motion, pressure and other sensors are essential. In data analyzing and motion control microprocessor plays important role. This article describes development of automated module for controlling the Lab High Vacuum System.
Keywords: vakuumski sistemi; računalniško krmiljenje; krmilni sistemi; avtomatizacija